Dealing with uncertainties in asteroid deflection demonstration missions: NEOTωIST. Issue Volume 10:Issue S318(2015) (1st March 2016) - Eggl, Siegfried; Hestroffer, Daniel; Cano, Juan L.; Ávila, Javier Martín; Drube, Line; Harris, Alan W.; Falke, Albert; Johann, Ulrich; Engel, Kilian; Schwartz, Stephen R.; Michel, Patrick
Abstract: Deflection missions to near-Earth asteroids will encounter non-negligible uncertainties in the physical and orbital parameters of the target object. In order to reliably assess future impact threat mitigation operations such uncertainties have to be quantified and incorporated into the mission design. The implementation of deflection demonstration missions offers the great opportunity to test our current understanding of deflection relevant uncertainties and their consequences, e.g., regarding kinetic impacts on asteroid surfaces. In this contribution, we discuss the role of uncertainties in the NEOTωIST asteroid deflection demonstration concept, a low-cost kinetic impactor design elaborated in the framework of the NEOShield project. The aim of NEOTωIST is to change the spin state of a known and well characterized near-Earth object, in this case the asteroid (25143) Itokawa. Fast events such as the production of the impact crater and ejecta are studied via cube-sat chasers and a flyby vehicle. Long term changes, for instance, in the asteroid's spin and orbit, can be assessed using ground based observations. We find that such a mission can indeed provide valuable constraints on mitigation relevant parameters. Furthermore, the here proposed kinetic impact scenarios can be implemented within the next two decades without threatening Earth's safety.